(untitled) (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Medication adherence is crucial for optimal health outcomes in chronic obstructive pulmonary disease (COPD). Non-adherence contributes to acute exacerbations, repeated hospitalizations, poor quality of life, increased healthcare costs, and higher morbidity and mortality. The objective of this study was to assess the level of adherence to medication among patient with COPD attending outpatient department (OPD) of Patan Hospital, Nepal. Method: A cross-sectional analytical study conducted in Medical OPD of Patan Hospital from 2019 Sep 1 to Nov 9. A total of 240 patients with COPD were selected using purposive sampling technique. Data were collected through face-to-face interview with a structured questionnaire that included patient characteristics and the standardized Morisky Green Levine Medication Adherence Scale. Data were analysed using descriptive statistics and chi-square test for association. Ethical approval was obtained from the Institutional Review Committee of Patan Academy of Health Sciences. Result: Among 240 respondents, 31.25% demonstrated high adherence to medication, 48.8% had medium adherence and 20% had low adherence. A significant association was observed between route of medication administration and level of adherence (p=0.020). Conclusion: Only about one-third of COPD patients had high adherence to medication. Programs to improve adherence should consider factors influencing patient behaviour, particularly the route of medication administration, to reduce exacerbations and improve health outcomes.